The impact of carbon dioxide and other greenhouse gases on forest ecosystems. Report No.3 of the IUFRO task force on environmental change - Karnosky, D. F.; Ceulemans, R.; Ceulemans, R.; Innes, J. L.; Innes, J. L.; Karnosky, D. F.; Scarascia-Mugnozza, G. E.; Scarascia-Mugnozza, G. E. (Wallingford :CABI Publishing, 2001)
This book, which will be of interest to advanced students and researchers in forestry, tree physiology and ecology, climate change and pollution, includes 11 chapters which review what is known about the impacts of elevated CO2 and other greenhouse gases on forest ecosystems.
Keywords: FF060 - Plant Physiology and Biochemistry; KK100 - Forests and Forest Trees (Biology and Ecology); PP500 - Meteorology and Climate; PP600 - Pollution and Degradation